Electrochemical performance of crumpled graphene loaded with magnetite and hematite nanoparticles for supercapacitors. (May 2017) - Lee, Chongmin; Jo, Eun Hee; Kim, Sun Kyung; Choi, Ji-Hyuk; Chang, Hankwon; Jang, Hee Dong
Abstract: Iron oxides have emerged as alternative electrode materials for supercapacitors because they have advantages of low cost, natural abundance, and environmental friendliness. Graphene loaded with hematite (Fe2 O3 ) or magnetite (Fe3 O4 ) exhibited enhanced specific capacitance as well as a high energy density. In this study, we present three-dimensional (3D) crumpled graphene (CGR) decorated with Fe2 O3 and Fe3 O4 nanoparticles to determine which one can exhibit higher electrochemical performance of supercapacitors. The 3D CGR-Fe2 O3 and 3D CGR-Fe3 O4 composites were synthesized in different gas atmospheres from a colloidal mixture of GO and from iron (III) chloride hexahydrate (FeCl3 ·6H2 O), respectively, via one step aerosol spray pyrolysis. Sizes of both iron oxides nanoparticles were ranged from 5 to 10 nm when loaded onto 500 nm CGR. The electrochemical properties of the 3D CGR-Fe2 O3 and 3D CGR-Fe3 O4 composites were examined to compare the electrochemical performance of both composite electrodes. The 3D CGR-Fe3 O4 composite electrode had higher values of capacitance and electrical conductivity than those of the 3D CGR-Fe2 O3 composite electrode. Graphical abstract: Highlights: Crumpled graphene loaded with magnetite and hematite was synthesized, respectively. High electrochemical performance was obtained using both iron oxides-CGR. Magnetite-CGR showed higher electrochemical performance than hematite-CGR.